PELATIHAN PEMBUATAN TEH HERBAL ANTIDIABETES DAN ANTIHIPERTENSI DARI SEMBILAN REMPAH BAGI IBU-IBU PERSEKUTUAN WANITA (PW) GKI BETHESDA MARIBU - Frans A. Asmuruf; Yuliana R. Yabansabra; Anna Rumabar (LPPM Uncen, 2018)
A mixture of nine spices consisting of nutmeg, ginger, cumin, pandanus, lemongrass, cinnamon, cloves, bay leaves and white turmeric is one of the innovations in the use of plants which are commonly used as cooking spices processed into herbs for traditional medicine. Previous studies reported that nine spices tea has the properties and benefits of lowering blood sugar levels for patients with Type II diabetes and able to reduce blood pressure for high blood pressure (hypertension). To inform the community of the benefits of nine spices tea to be used as a health drink for families, socialization and practice of the Nine Spices tea making have been carried out for housewives gathered of GKI Bethesda Maribu. Maribu village, located in Sentani Barat District, was chosen as the location of the socialization because, based on interviews and health data, there were cases of diabetes and hypertension that had been reported. The result obtained from this activity is that there has been a transfer of knowledge about processing spices into traditional medicine. The community testified that making nine spices tea and consume it at home benefit for their health.Keywords: Maribu, Testimoni, traditional medicine